Calf circumference has a positive correlation with physical performance among community-dwelling middle-aged, older women - Wang, Po-Chun; Yeh, Wei-Chung; Tsai, Yi-Wen; Chen, Jau-Yuan (Frontiers in Public Health, 2022)
Introduction Sarcopenia and frailty are well-known public health problems in middle-aged and older people. Calf circumference (CC) is a representative anthropometric index that may be useful for screening sarcopenia. Physical performance, assessed by hand grip strength and gait speed, measures sarcopenia and frailty. This community-based, cross-sectional study was conducted in Guishan District, Taoyuan City, between April and October 2017 to investigate the relationship between CC and physical performance among community-dwelling middle-aged, older people in Taiwan and to evaluate potential sex differences. CC tends to be an efficient predictor of physical performance in community health screenings and outpatient clinics for community health examinations, where there is limited time for surveys. Methods A total of 1,308 volunteers aged 50–85 were recruited. Volunteers who declined to participate, those with recent cardiovascular disease, and those with an inability to complete an interview, physical performance examinations, and body composition measurements were excluded from the study. A total of 828 participants were enrolled in this study (237 men and 591 women). The statistical methods applied in this study were the Mann–Whitney U-test, independent two-sample t-test, Chi-square test, and multivariate logistic regression models. Result and discussion Significant differences were observed in age, waist circumference, appendicular skeletal mass index, calf circumference, hand grip strength, and income between men and women. No significant differences were observed between the men and women regarding body mass index, gait speed, exercise habits, or underlying disorders of diabetes mellitus, hypertension, or hyperlipidemia. Comparing across three different CC tertiles, we discovered significant differences in age, body mass index, waist circumference, appendicular skeletal muscle index, gait speed, and hand grip strength in both men and women. On multivariate logistic regression, after adjusting for age, appendicular skeletal mass index, body mass index, exercise habits, income levels, and CC were positively correlated with physical performance as measured by both gait speed (β = 0.15, p = 0.01) and hand grip strength (β = 0.25, p < 0.001) in women, compared to only hand grip strength (β = 0.41, p < 0.001) in men. Lower calf circumference is an independent risk factor for poor physical performance, especially among women.